Structure Design for Ultrahigh Power Density Proton Exchange Membrane Fuel Cell. Issue 3 (6th January 2023) - Zhang, Guobin; Wu, Lizhen; Tongsh, Chasen; Qu, Zhiguo; Wu, Siyuan; Xie, Biao; Huo, Wenming; Du, Qing; Wang, Huizhi; An, Liang; Wang, Ning; Xuan, Jin; et al.
Abstract: Next‐generation ultrahigh power density proton exchange membrane fuel cells rely not only on high‐performance membrane electrode assembly (MEA) but also on an optimal cell structure. To this end, this work comprehensively investigates the cell performance under various structures, and it is revealed that there is unexploited performance improvement in structure design because its positive effect enhancing gas supply is often inhibited by worse proton/electron conduction. Utilizing fine channel/rib or the porous flow field is feasible to eliminate the gas diffusion layer (GDL) and hence increase the power density significantly due to the decrease of cell thickness and gas/electron transfer resistances. The cell structure combining fine channel/rib, GDL elimination and double‐cell structure is believed to increase the power density from 4.4 to 6.52 kW L −1 with the existing MEA, showing nearly equal importance with the new MEA development in achieving the target of 9.0 kW L −1 . Abstract : The cell structure combining fine channel/rib, gas diffusion layer elimination and double‐cell structure is believed to increase the power density of proton exchange membrane fuel cell from 4.4 to 6.52 kW L −1 with the existing membrane electrode assembly (MEA), showing nearly equal importance with the new MEA development in achieving the next‐generation fuel cell of ultrahigh power density.